2018
DOI: 10.2528/pierm18090504
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Electric Coupling Analysis for Angular Misalignment of Spiral Resonators in WPT Systems

Abstract: Angular misalignment is an issue for many potential applications of wireless power transfer (WPT). It is necessary to keep coupling coefficient, especially the magnetic coupling to be insensitive to angular misalignment. This paper analyzes the coupling between the spiral resonators when one resonator rotates with respect to the other. The quantitative data of magnetic and electric coupling components as well as the total coupling coefficient in angular misalignments are presented. Furthermore, a 3D spiral res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This study is an extension of our previous work reported in [17]. The study proposes an omnidirectional resonator which can keep coupling at a certain level when it rotates around all x, y, and z axes.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…This study is an extension of our previous work reported in [17]. The study proposes an omnidirectional resonator which can keep coupling at a certain level when it rotates around all x, y, and z axes.…”
Section: Introductionmentioning
confidence: 84%
“…It is necessary to understand the magnetic and electric coupling components for these two basic resonators. In our previous study, we analyzed the dependence of coupling on alignment angle for spiral resonator and showed that the magnetic coupling component was 0 when two spiral resonators were in perpendicular positions [17]. In this study, we give an example of the coupling analysis on helical resonators to indicate the coupling dependence on the alignment angle.…”
Section: Coupling Dependence On Alignment Anglementioning
confidence: 90%
See 3 more Smart Citations